Uncertainty and Malaysian financial markets / Joel Raj Francis - Francis, Joel Raj (Universiti Teknologi MARA, Negeri Sembilan, 2023)
This study examines the long run cointegration relationship of two uncertainty indices namely the Global Economic Policy Uncertainty (GEPU) and Geopolitical Risk (GPR) on the returns of Malaysian stock and commodity market for the period from January 2000 to December 2022. The Malaysian stock market is represented by the Bursa Malaysia Kuala Lumpur Composite Index (KLCI) whilst the Malaysian commodity market is represented by the Bursa Malaysia Crude Palm Oil Futures (FCPO). The Autoregressive Distributed Lag (ARDL) approach is used to analyze the possible long-run cointegration between the uncertainty indices and the stock and commodity market's return. Our findings show that GEPU has a significant impact on the stock market and commodity market returns. We discover that GEPU has a significantly negative impact on the returns of the stock and commodity market over the long run. GPR, on the other hand, positively affects the return of stock market and negatively affects the return of commodity market in the long run. According to the findings, it is strongly advised that investment managers and investors in the Malaysian stock and commodity markets pay greater attention to the volatility of GEPU and GPR both in the short run and in the long run in order to control the risk of return in the stock and commodity market. In addition, policymakers should be strongly encouraged to keep a careful eye on the movement of the GEPU and GPR index, since this indicator is a significant factor in determining the returns of the Malaysian financial markets.